Torsadogenic potential of a novel remyelinating drug clemastine for multiple sclerosis assessed in the rabbit proarrhythmia model - Satoshi Kawakami; Yoshinobu Nagasawa; Mihoko Hagiwara-Nagasawa; Kensuke Omura; Megumi Aimoto; Akira Takahara (Elsevier, 2020)
We assessed the torsadogenic effects of a novel remyelinating drug clemastine for multiple sclerosis using an in vivo proarrhythmia model of acute atrioventricular block rabbit, since the drug has been demonstrated to suppress the human ether-á-go-go related gene (hERG) K+ channels. Bradycardia was induced by atrioventricular node ablation in isoflurane-anesthetized New Zealand White rabbits (n = 5), and the ventricle was electrically driven at 60 beats/min throughout the experiment, except when extrasystoles appeared. Intravenous administration of clinically relevant dose of 0.03 mg/kg of clemastine and 10-times higher dose of 0.3 mg/kg hardly affected the QT interval or duration of the monophasic action potential (MAP) of the ventricle. Additional administration of clemastine at 3 mg/kg significantly increased the QT interval, MAP duration and the short-term variability of repolarization. Meanwhile, the premature ventricular contractions with R on T phenomenon were observed in 3 out of 5 animals, and torsades de pointes arrhythmias were detected in 1 out of 5 animals. These results suggest that the torsadogenic potential of clemastine is obviously observed in the acute atrioventricular block rabbit, which will not appear within the prescribed dose for multiple sclerosis.